Simple Liver Cyst as a Focus of Salmonella paratyphi Abscess: A Case Report - A. Sangwaiya; A. Patel; J. Chan; J. Arnold (Journal of Tropical Medicine)
Salmonellosis, endemic in various part of the world, is considered a differential diagnosis in a tropical traveller. Although it usually presents as gastroenteritis, its various clinical syndromes may vary from mild gastroenteritis to severe septicaemia including abscess formation, the later two being the most common cause of morbidity and mortality. Here we present a patient who returned to the UK after an overseas trip and was diagnosed with a pyogenic liver abscess with Salmonella paratyphi at a site of a pre-existing simple liver cyst.